'No time for health:' exploring couples' health promotion in Indian slums. (24th December 2018) - Gaiha, Shivani Mathur; Gillander Gådin, Katja
Summary: Joint involvement of couples is an effective strategy to increase contraceptive use and improve reproductive health of women. However, engaging couples to understand how their gender attitudes affect their personal and family health is an idea in search of practice. This mixed-methods study explores opportunities and barriers to couples' participation in health promotion in three slums of Delhi. For each couple, surveys and semi-structured interviews were conducted with husbands and wives individually to contrast self and spousal work, time, interest in health, sources of information related to health and depth of knowledge ( n  = 62). Urban poverty forces men to work long hours and women to enter part-time work in the informal sector. Paid work induces lack of availability at home, lack of interest in health information and in performing household chores and a self-perception of being healthy among men. These factors inhibit men's' participation in community-based health promotion activities. Women's unpaid work in the household remains unnoticed. Women were expected to be interested in and to make time to attend community-based health-related activities. Men recalled significantly less sources of health information than their spouse. Men and their wives showed similar depth of health-related knowledge, likely due to their spousal communication, with women acting as gatekeepers. Health promotion planners must recognize time constraints, reliance on informal interpersonal communication as a source of health information and the need to portray positive masculinities that address asymmetric gender relations. Innovative, continuous and collaborative approaches may support couples to proactively care about health in low-resource settings.